Evidence From Family Studies for Autoimmunity in Arrhythmogenic Right Ventricular Cardiomyopathy: Associations of Circulating Anti-Heart and Anti-Intercalated Disk Autoantibodies With Disease Severity and Family History. Issue 15 (14th April 2020) - Caforio, Alida L.P.; Re, Federica; Avella, Andrea; Marcolongo, Renzo; Baratta, Pasquale; Seguso, Mara; Gallo, Nicoletta; Plebani, Mario; Izquierdo-Bajo, Alvaro; Cheng, Chun-Yan; Syrris, Petros; Elliott, Perry M.; et al.
Abstract : Background: Serum anti-heart autoantibodies (AHAs) and anti-intercalated disk autoantibodies (AIDAs) are autoimmune markers in myocarditis. Myocarditis has been reported in arrhythmogenic right ventricular cardiomyopathy (ARVC). To provide evidence for autoimmunity, we searched for AHAs and AIDAs in ARVC. Methods: We studied: 42 ARVC probands, 23 male, aged 42, interquartile range 33–49, 20 from familial and 22 nonfamilial pedigrees; 37 clinically affected relatives (ARs), 24 male aged 35, interquartile range 18–46; and 96 healthy relatives, 49 male, aged 27, interquartile range 17–45. Serum AHAs and AIDAs were tested by indirect immunofluorescence on human myocardium and skeletal muscle in 171 of the 175 ARVC individuals and in controls with noninflammatory cardiac disease (n=160), ischemic heart failure (n=141), and healthy blood donors (n=270). Screening of 5 desmosomal genes was performed in probands; when a sequence variant was identified, cascade family screening followed, blind to immunologic results. Results: AHA frequency was higher (36.8%) in probands, ARs (37.8%), and healthy relatives (25%) than in noninflammatory cardiac disease (1%), ischemic heart failure (1%), or healthy blood donors (2.5%; P =0.0001). AIDA frequency was higher in probands (8%, P =0.006), in ARs (21.6%, P =0.00001), and in healthy relatives (14.6%, P =0.00001) than in noninflammatory cardiac disease (3.75%), ischemic heart failure (2%), or healthy blood donors (0.3%). AHA-positive status was associated with higher frequency of palpitation ( P =0.004), implantable cardioverter defibrillator implantation ( P =0.021), lower left ventricular ejection fraction ( P =0.004), AIDA-positive status with both lower right ventricular and left ventricular ejection fractions ( P =0.027 and P =0.027, respectively). AHA- and/or AIDA-positive status in the proband and at least one of the respective relatives was more common in familial (17/20, 85%) than in sporadic (10/22, 45%) pedigrees ( P =0.007). Conclusions: The presence of AHAs and AIDAs provides evidence of autoimmunity in the majority of familial and in almost half of sporadic ARVC. In probands and in ARs, these antibodies were associated with features of disease severity. Longitudinal studies are needed to clarify whether they may predict ARVC development in healthy relatives or if they be a result of manifest ARVC. Abstract : Supplemental Digital Content is available in the text.